2010
DOI: 10.1016/j.jep.2010.02.028
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguity of khat in Somaliland

Abstract: The article argues that khat has both negative and positive effects on Somaliland society. Comparing the role of khat in Somaliland with khat in Puntland and South-central Somalia it is clear that khat in itself does not determine if it contributes to state building and peace, or state failure and violence. Rather, it is the socio-cultural, political and historical context in which it is consumed that determines its larger societal effects. A nuanced analysis of the positive and negative aspects of khat that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…More than 70% of khat chewers were younger than 35 years, and the unemployment rate was 62% among khat chewers. This is in accordance with the opinions reported by other studies, which have reported that excessive khat use is associated with reduced productivity and risk of unemployment because khat reduces motivation of work and increases the occurrences of work absenteeism [8,46,47]. …”
Section: Discussionsupporting
confidence: 92%
“…More than 70% of khat chewers were younger than 35 years, and the unemployment rate was 62% among khat chewers. This is in accordance with the opinions reported by other studies, which have reported that excessive khat use is associated with reduced productivity and risk of unemployment because khat reduces motivation of work and increases the occurrences of work absenteeism [8,46,47]. …”
Section: Discussionsupporting
confidence: 92%
“…In the traditional khat chewing areas, chewing is mostly not a solitary practice 60–62. People chew khat in the company of friends discussing issues deemed important by the chewers 60,61. Hence, as Hansen61 noted, some chewers may attend chewing sessions mainly for socialization while not much interested in the chewing.…”
Section: Discussionmentioning
confidence: 99%
“…People chew khat in the company of friends discussing issues deemed important by the chewers 60,61. Hence, as Hansen61 noted, some chewers may attend chewing sessions mainly for socialization while not much interested in the chewing. As also shown by the present and other studies,62 socialization is one of the reasons ascribed to khat chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Qaad is a mild stimulant which most Somali males chew in the afternoon hours; it is a central means of forging social and political ties in northern Somalia. 58 Influential figures are expected to regularly hand out qaad to their relatives and followers. Generosity, an important characteristic of any Somali leader, was traditionally expressed by slaughtering a goat for the guests.…”
Section: Different Types Of Traditional Authoritiesmentioning
confidence: 99%